Training of coordinators of Sports for Everyone - José Antonio Rebollo González; Pedro Sáenz-López Buñuel (FEADEF, 2010)
With the data obtained in the diagnosis of the current situation of training «Sport for All», regarding the base of the structure of the courses that were conducted in our Province and after the literature review that was conducted, we have created a new course of coordinators of Sports for Everyone. There have been modifications in all curricular elements, always trying to adapt the training of animators to the current situation and trying to align the structure to the training of any sport's professional. In this regard, we have increased the content being taught in the present, dividing them into a common and a specific block. The objectives have been formulated under the new design. It has been put in place a methodology agreed with the teachers, with a schedule for meetings as for the theoretical and as well as for the practical subjects. We have tried to unify the evaluation strategies to fit consistency with the proposed methodology. The planning was done according to the Order 3310/2002, which regulates the training of sports.